Radiological characteristics of glioblastoma multiforme using CT and MRI examination. Issue 1 (January 2019) - Abd-Elghany, Amr A.; Naji, Abdu Ahmed; Alonazi, Batil; Aldosary, Hassan; Alsufayan, Mohammed Abdluaziz; Alnasser, Mohammed; Mohammad, Ebtsam A.; Mahmoud, Mustafa Z.
ABSTRACT: The purpose of this study was to describe, analyze and characterize computed tomography (CT) and magnetic resonance imaging (MRI) scan of glioblastoma multiforme (GBM) patients. One hundred and three clinically definite GBM patient information, CT and MRI images along with clinical records and demographic data were retrospectively collected from the radiology information system (RIS) database of the Radiology and Medical Imaging Department of King Fahd Medical City between January 2012 to March 2019. Based on our analysis, 70.9% and 29.1% were males and females patients with a mean age of 49.05 ± 14.77 years. The majority of patients (98.1%) were diagnosed with GBM by MRI T2-weighted fluid attenuation inversion recovery (FLAIR) hyperintense scanning protocols, 97.1% diagnosed by MRI T2-weighted hyperintense and 93.2% were diagnosed by an MRI T1-weighted hypointense. About 98.1% of patients had MRI contrast enhancement while 88.1% and 6.8% had a CT hypodense and heterogeneous appearance, respectively. GBM shape in 100% of patients was irregular and the majority (41.8%) of GBM were located in the frontal lobe. In conclusion, this study manages to describe, analyze and characterize the radiological features of GBM in CT and MRI examination.